2012
DOI: 10.1007/s00213-012-2902-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of orexin/hypocretin in conditioned sucrose-seeking in rats

Abstract: Rationale The orexin/hypocretin system has recently been implicated in reward-seeking, especially for highly salient food and drug rewards. We reasoned that this system may be strongly engaged during periods of reward restriction, including food restriction. Objectives This study examined the involvement of the orexin (Orx) system in responding for sucrose, and in cue-induced reinstatement of extinguished sucrose-seeking, in ad libitum fed vs. food-restricted male subjects. Methods Sprague Dawley rats (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 69 publications
(106 reference statements)
12
100
4
Order By: Relevance
“…Neither SB-334867, nor the selective OX 2 receptor antagonist TCS OX2 29 [53] reduce cue-induced reinstatement of food pellet-seeking [138]. Other studies have shown that there is a reduction in sucrose pellet-seeking (FR1) and reinstatement following OX 1 receptor antagonism (SB-334867), but only in food restricted rats [175]. In contrast, the same OX 1 receptor antagonist reduces self-administration of 1 % saccharin pellets and cue-induced reinstatement in both food restricted and sated rats [176].…”
Section: Natural and Synthetic Reward Discriminationmentioning
confidence: 94%
“…Neither SB-334867, nor the selective OX 2 receptor antagonist TCS OX2 29 [53] reduce cue-induced reinstatement of food pellet-seeking [138]. Other studies have shown that there is a reduction in sucrose pellet-seeking (FR1) and reinstatement following OX 1 receptor antagonism (SB-334867), but only in food restricted rats [175]. In contrast, the same OX 1 receptor antagonist reduces self-administration of 1 % saccharin pellets and cue-induced reinstatement in both food restricted and sated rats [176].…”
Section: Natural and Synthetic Reward Discriminationmentioning
confidence: 94%
“…Mice lacking the OX gene, compared to wild-type mice, consume less sucrose when available ad libitum , even after accounting for differences in their locomotor activity (Matsuo et al, 2011). A role for the OX1R in mediating intake of palatable food is supported by the findings that systemic injection of the OX1R antagonist, SB-334867, reduces operant responding for both sucrose and saccharin pellets, in a minimal work paradigm with a fixed ratio 1 schedule (Cason & Aston-Jones, 2013a, 2013b, 2014). This antagonist also suppresses binge-like intake of sucrose, saccharin, and fructose solutions under an intermittent-access home cage drinking paradigm (Alcaraz-Iborra, Carvajal, Lerma-Cabrera, Valor, & Cubero, 2014; Rorabaugh, Stratford, & Zahniser, 2014) and reduces intake of a high-fat diet under both ad libitum and limited-access feeding paradigms (Choi, Davis, Fitzgerald, & Benoit, 2010; Valdivia, Patrone, Reynaldo, & Perello, 2014; White et al, 2005).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 95%
“…The involvement of endogenous OX in the performance of this task is suggested by the findings that ventricular injection of OX-A increases the breakpoint for sucrose (Choi et al, 2010; Kay et al, 2014), while peripheral injection of the OX1R antagonist SB-334867 reduces the breakpoint for sucrose (Cason & Aston-Jones, 2013b; Espana et al, 2010), high-fat diet (Borgland et al, 2009), and sweet-fat pellets (Choi et al, 2010). The specific brain site involved in this response has yet to be identified, with OX-A in the ventral tegmental area failing to affect the breakpoint for sucrose (Terrill et al, 2016) and knockdown of the OX1R in the paraventricular thalamus failing to affect breakpoint for high-fat diet (Choi et al, 2012).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
See 1 more Smart Citation
“…LH orexin cells are activated by environmental cues that predict highly rewarding food stimuli, and 3 rd -icv orexin-A not only increases food intake but also increases operant responding for palatable food on a PR schedule [57]. Conversely, peripheral injection of the selective OX1R antagonist SB334867 reduces PR responding for palatable food reinforcement [57-59]. The orexin projection to the VTA, in particular, has been suggested to play a role in palatable food intake.…”
Section: A More Integrated Perspectivementioning
confidence: 99%